(untitled) (Fiep Bulletin - online, 2025)
Objective: to analyze the importance of the numismatic and philatelic collection for the professor. physical education and sports. Introduction: The presence of numismatic and philatelic collections for the professor. of physical education and sports in Brazil and around the world is an important fact, due to launches during the Copa Américas, Pan-Americans, World Cups, Paralympics and Olympics. Here in Brazil, coins, banknotes and stamps have been part of museum collections since the founding of the first museums, with the first museum dedicated exclusively to numismatics being founded at the end of the 19th century. Coins are witnesses of history and serve to tell the story of humanity from its invention, at the end of the 6th century BC to the last Olympics in Paris 2024. Methodology: Through stages such as cataloguing, analysis and meaning for professors. Physical Education and Sports. Carry out the survey between 1990 and 2024. Results: it was observed that major sporting events motivate the public sector to launch coins and stamps. Attracting the public to save, remember and collect, especially those directly related to sports. Conclusion: Through museums, exhibitions, clubs, interest and continuity in the collection of coins, cells and stamps by professors increase. physical education and sports, who experience the noble values of sport and keep its memories.